39 Overview of tricuspid regurgitation (tr). new classification of tr. when severe tr is too severe?. (17th January 2020) - Vieitez Florez, J M; Monteagudo, J M; Mahia, P; Perez, L; Lopez, T; Marco, I; Perone, F; Gonzalez, T; Sitges, M; Bouzas, A; Gonzalez, V; Li, P; et al.
Abstract: Introduction: Tricuspid regurgitation (TR) importance is growing in the last years. Its presence is associated with a worse prognosis. A new severity classification has been published, adding massive and torrential to the classical TR classification. However, it is not know how many of the patients classified as severe TR, corresponds to the new Torrential or massive classification that for sure will lead to different treatment strategies. Also few published studies have addressed the aetiologies, mechanisms and severity in large cohorts. Purpose: To evaluate the burden of TR in a large cohort of patients referred for an echocardiography. Methods: Prospective study where consecutive patients undergoing an echocardiographic study in 10 Spanish hospitals within a three-month period were included. All studies with at least moderate TR were selected for analysis. The evaluation was conduced according to the usual practice of the laboratory. TR assessment was performed as recommended by the European Association of Cardiovascular Imaging. TR was quantified according to Hanh & Zamorano new published classification. Results: A total of 35088 consecutive echocardiographic studies were performed in the participant hospitals during the recruitment period. TR of at least moderate degree was detected in 2124 studies (6, 05%). Mean age was 77, 1 years and 62.8% were women. Mitral or aortic valvulopthy was the most common cause, present in almost half of cases (48.4%). The second cause of TR was idiopathic with 22.2% of cases. Primary TR was found in 7.2% of patients, the most frequent aetiology in these group was cardiac implantable devices with 4.2% of total of TR. Aetiology and severity according to the new classification can be seen in the figures Atrial fibrillation was present in 47.6% of cases. 56.4% of patients had symptoms at the time of the study (NYHA≥2 at the time of study). Right ventricle (RV) was dilated (telediastolic basal diameter >42mm) in 39.4% of patients). RV function was impared (TAPSE <17mm) in 30.6% of patients. Conclusions: In these larger multicentre study, significant TR may is present in up to 6% of the echocardiographic studies and is often symptomatic[m1] . 4, 91% of patients had a massive or torrential grade. Most TR are secondary to mitral or aortic valvulopathy. Idiopathic TR has taken the second place.